The Effect of Fragaria vesca Extract on Smear Layer Removal: A Scanning Electron Microscopic Evaluation - Davoudi, Amin; Razavi, Sayed Alireza; Mosaddeghmehrjardi, Mohammad Hossein; Tabrizizadeh, Mehdi (Iranian Endodontic Journal, 2015)
Introduction: Successful endodontic treatment depends on elimination of the microorganisms through chemomechanical debridement. The aim of this in vitro study was to evaluate the effectiveness of Fragaria vesca (wild strawberry) extract (FVE) on the removal of smear layer (SL). Methods and Materials: In this analytical-observational study, 40 extracted mandibular and maxillary human teeth were selected. After canal preparation with standard step-back technique, the teeth were randomly divided into 4 groups according to the irrigation solution: saline (negative control), 5.25% NaOCl+EDTA (positive control), FVE and FVE+EDTA. The teeth were split longitudinally so that scanning electron microscopy (SEM) photomicrographs could be taken to evaluate the amount of remnant SL in coronal, middle and apical thirds. The data were analyzed statistically by the Kruskal-Wallis and Mann Whitney U tests and the level of significance was set at 0.05. Results: Significant differences were found among the groups (P<0.001). The use of NaOCl+EDTA was the most effective regimen for removing the SL followed by FVE+EDTA. FVE alone was significantly more effective than saline (P<0.001). Conclusion: FVE with and without EDTA could effectively remove the smear layer; however, compared to NaOCl group it was less effective. Keywords: Fragaria vesca; Irrigation; Scanning Electron Microscopy; Smear Layer